TNFα, IL-6, miR-103a-3p, miR-423-5p, miR-23a-3p, miR-15a-5p and miR-223-3p in the crevicular fluid of periodontopathic patients correlate with each other and at different stages of the disease - Erica Costantini; Bruna Sinjari; Pamela Di Giovanni; Lisa Aielli; Sergio Caputi; Raffaella Muraro; Giovanna Murmura; Marcella Reale (Scientific Reports, 2023)
Abstract Periodontitis is one of the main frequent intraoral diseases. Pathogenesis triggers are the immune responses with pro-inflammatory cytokines production and non-coding RNAs expression. The purpose of the present study was to evaluate the involvement of selected miRNAs in various stages of periodontitis and their relationship with the levels of inflammatory mediators in gingival crevicular fluid (GCF). For this study, 36 subjects (21 with periodontal disease, 15 healthy controls) were selected with an age mean of 59.1 ± 3.7 years. Clinical parameters included plaque index, gingival index, sulcus bleeding index, pocket depth, and clinical attachment level. The GCF samples were taken using capillary paper. The levels of miRNAs in GCF were estimated using a Real-Time PCR and TNFα and IL-6 levels were assessed by enzyme-linked immunosorbent assay (ELISA). The results indicated that the miRNA-103a-3p, miRNA-23a-3p, miRNA-15a-5p, and miRNA-223-3p were significantly upregulated with respect to healthy controls. Significant differences were observed for miRNA-23a-3p, miRNA-103a-3p and miRNA-423-5p levels in accord with the disease stages. Inflammatory mediators evaluated in GCF correlate well with the clinical parameters and the severity of the periodontal disease. miRNAs can represent biomarkers of disease stage and can be investigated as a possible therapeutic target, as well as levels of TNFα and IL-6 may drive the disease progression by acting as prognostic markers.